Pengaruh Kepemimpinan Transformasional Terhadap Budaya Sekolah di Lingkungan Korwil Karawaci Kota Tangerang dengan Motivasi Kerja Guru Sebagai Variabel Mediasi - Nugraheni, Bernadeth Septina; Kasmari, Kasmari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
A strong school culture is a key factor in improving the quality of education and teacher performance within the school environment. This study aims to analyze the influence of the principal's transformational leadership on school culture, with teacher work motivation as a moderating variable, in elementary schools in the Karawaci Regional Coordination area, Tangerang City. Transformational leadership is measured through three main dimensions: inspirational motivation, individual consideration, and intellectual stimulation. The study used a quantitative approach with a survey method, distributing questionnaires to teachers as respondents. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS SEM). The results show that all dimensions of transformational leadership have a positive and significant effect on teacher work motivation and school culture. Teacher work motivation has been shown to strengthen the influence of transformational leadership on school culture. The effectiveness of principal leadership in shaping a collaborative, disciplined, and innovative school culture will be further strengthened when supported by high levels of teacher work motivation.